Sexual Activity in Couples Dealing With Breast Cancer. A Cohort Study of Associations With Patient, Partner and Relationship-Related Factors - Rottmann, Nina; Larsen, Pia Veldt; Johansen, Christoffer; Hagedoorn, Mariët; Dalton, Susanne Oksbjerg; Hansen, Dorte Gilså (Frontiers in Psychology, 2022)
Objective. Breast cancer may profoundly affect a couple’s sex life. The present study examines whether patient-, partner- and relationship-related characteristics are associated with sexual activity of couples following breast cancer diagnosis in the treatment phase and over time. Methods. Women with breast cancer and their male cohabiting partners participated in a longitudinal study in Denmark. Logistic regression was used to examine associations of patient-, partner- and relationship-related characteristics at baseline (≤4 months following surgery) with couples’ sexual activity at baseline, 5 and 12 months later. The longitudinal analyses were stratified for couples’ sexual activity status at baseline. Results. A total of 722, 533 and 471 couples were included in the analyses at baseline, 5- and 12-months follow-up, respectively. Older age, depressive symptoms and lower vitality of patients were associated with lower odds of couples’ sexual activity at baseline; chemotherapy treatment and older age of patients were associated with lower odds at 5-months follow-up in couples who were not sexually active at baseline. Higher ratings of emotional closeness, affectionate behavior and satisfaction with dyadic coping were associated with higher odds for sexual activity at baseline and over time in couples who were sexually active at baseline. Conclusion. Sexual counseling during cancer treatment and rehabilitation should include a couple perspective. Relationship-related variables may be a protective factor for remaining sexually active after breast cancer diagnosis. Interventions could focus on strengthening these factors. Health professionals also need to consider the patients’ breast cancer treatment, vitality, and emotional distress in counselling on sexuality.